Radiation Characteristics Of A Coaxial Waveguide With Opposing Dielectric Filled Grooves - Hacıvelioğlu, Feray; Uzgören, Gökhan; Büyükaksoy, Alinur (Inst Engineering Technology-Iet, Michael Faraday House Six Hills Way Stevenage, Hertford Sg1 2Ay, England, 2010)
The purpose of the present study is to provide a rigorous analysis to the coaxial waveguide with two opposing grooves in the outer and inner cylinders with different depths and filled with different dielectric materials. The representation of the solution to the three-part mixed boundary-value problem in terms of Fourier integrals leads to a couple of simultaneous modified Wiener-Hopf equations that are reduced to infinite systems of linear algebraic equations. These systems are solved numerically and the bandstop filter characteristics of the reflection coefficient are studied in terms of frequency, groove sizes and the parameters of the filling dielectric material.
Keywords: Rectangular Grooves; Mode Scattering; Parallel-Plate; Discontinuity; Plane; Dikdörtgen Oyuklar; Mod Saçılması; Paralel Plaka; Devamsızlık; Uçak